(untitled) (Biological Sciences - PJSIR, 2022)
Extraction of acetic acid produced from esterification of fusel oil with acetic anhydride was experimentaJIy investigated. The selective solvent used to extract the formed acetic acid was water. Solubility data and equilibrium curves for ternary system (water-acetic acid-acetates) were experimentaJIy determined. The results have provided useful data in designing and operating the counter-current multistage extraction unit.